8B.02: EFFECTS OF LONG-TERM BAROREFLEX ACTIVATION IN CONGESTIVE HEART FAILURE. (June 2015) - Seravalle, G.; Gronda, E.; Trevano, F. Quarti; Dell'Oro, R.; Costantino, G.; Casini, A.; Alsheraei, A.; Lovett, E.; Vanoli, E.; Mancia, G.; Grassi, G.
Abstract : Objective: It is well known that congestive heart failure (CHF) is characterized by an increased adrenergic tone and by an impaired baroreflex sympathetic and vagal control. In recent years have been developed additional therapeutic options, baroreflex activation therapy (BAT), capable to antagonize the sympathetic overactivity. It has been reported in CHF patients a significant reduction in muscle sympathetic nerve activity (MSNA) after 6 months BAT. Whether the effects on sympathetic and clinical variables were maintained chronically is unknown. Design and method: Eleven CHF patients (NYHA class III, left ventricular ejection fraction < 40%, with optimized and stable medical therapy and no active resinchronization therapy) have been evaluated at baseline and after 6 and 24 months BAT follow-up. During each step we collected clinical parameters, HYHA class, six-minute hall walk distance (6MHW), quality of life from the Minnesota Living with Heart Failure Questionnaire score (QOL), LVEF (3D echo), B-type natriuretic peptide (BNP), estimated glomerular filtration rate (eGFR), MSNA by microneurography, and baro reflex sensitivity (variated Kienbaum's method). Results: Two patients died during long-term follow-up (pneumoniae and acute HF). In the surviving 9 the beneficial effects observed at 6 months (MSNA -28%; BRS +100%; 6MWD +22.7%; LVEF +10%; QOL +37.2%) were maintained 21.5 ± 4.2 months (MSNA -31.6%, p < 0.001; BRS +100%, p < 0.001; 6MWD +19%, p = 0.01; LVEF +2.4%, p < 0.01; QOL +42.7%p < 0.01). A slight but not significant reduction was observed in blood pressure, heart rate, BNP and eGFR values. Hospitalization was not necessary after BAT. Conclusions: BAT provides long-term reduction in sympathetic activity and improvement in baroreflex sensitivity. This is accompanied by an improvement in clinical status, quality of life and functional capacity and by a reduction in rates of hospitalization.